Pengaruh Pemberian EVOO Terhadap Berat Badan Lahir Tikus Putih (Rattus norvegicus) pada Induk Model Preeklampsia - Evi Irianti; Syafruddin Ilyas; Rosidah Rosidah; Salomo Hutahaen; Ramlan Silaban (FORIKES, 2020)
Pre eclampsia is believed to be caused by a missmatch of antioxidants in the body which can be prevented by the administration of EVOO. EVOO which is proved to be rich in tocopherol which plays an important role in preventing this missmatch, thus both free radicals and antioxidants are in balanced concentration, particularly during pregnancy. This study was a laboratory based pre and post test with control group design which was conducted in total of 25 pregnant female albino rats from Sprague Dawley strain with body weight of approximately 200 grams. Samples were then grouped into P0 as control group and other 4 experimental group (P1, P2, P3, P4). Experimental group was given injection of 6% sodium chloride solution as much as 3 ml/day on the 6th until 12th day of their pregnancy and was given stimulation of acute stress on day 18th to model these groups into having pre eclampsia. All these four groups were then given EVOO on day 13th to 19th, except P1. On day 20th, all samples were executed. We found that birth weight among rats within experimental groups which were given either mild or moderate dose of EVOO showed no significant difference compared to control group, 71,43% fetus was found dead in P1, and 41,94% was found in P4. Thus, we concluded that EVOO was able to suppress free radicals and we suggested that other natural antioxidants, such as GPx, GSH and vitamin E should be furtherly investigated to see how these antioxidants work in altering the lipid peroxidation process after the administration of EVOO. Keywords: EVOO; birth weight ABSTRAK Salah satu penyebab preeklampsia adalah ketidak seimbangan antioksidan di dalam tubuh dan dapat dicegah dengan pemberian EVOO. Pemberian EVOO yang kaya akan kandungan tokoferol bertujuan untuk mencegah ketidakseimbangan antara produksi radikal bebas dan antioksidan khususnya pada kondisi hamil. Rancangan penelitian ini pre and post test with control goup design di laboratorium. Subyek tikus putih betina bunting, galur Sprague Dawley, BB ±200g. Total sampel 25 ekor terdiri atas kelompok kontrol (P0) dan 4 kelompok perlakuan sebagai model preeklampsia (P1, P2, P3, P4). Model preeklampsia dilakukan dengan injeksi NaCl 6% 3 ml/hari pada hari ke 6 – 12 periode kebuntingan dan stres akut hari ke18 sekali saja. Seluruh kelompok perlakuan diberi EVOO kecuali P1, dari hari ke 13 - 19. Hari ke 20, seluruh tikus dieksekusi. BBL kelompok perlakuan yang diberi EVOO dosis rendah maupun sedang tidak beda dengan kontrol, 71,43% fetus mati pada kelompok P1, dan 41,94% pada P4. Kesimpulan EVOO mampu menekan radikal bebas dalam darah. Disarankan untuk mengukur antioksidan alami lainnya seperti GPx, GSH serta vitamin E untuk mengetahui peranan dalam mereduksi peroksida lemak setelah pemberian EVOO. Kata kunci: EVOO; berat badan lahir